Effect of crop rotation on distribution pattern of arbuscular mycorrhizal fungal and microbial population - Sarita; Narender Singh; Rakesh Kumar Chugh; Kumar, Sunil; Sumit Kumar Aggarwal; Harmanjot Kaur; Sajad Un Nabi (Journal of Cereal Research, 2024)
In agriculture, a sequential cropping strategy is used to reduce soil pathogens and increase the productivity of next crops. It can, however, also affect the microbial populations in the soil, which is advantageous for plant development and arbuscular mycorrhizal fungi (AMF). For measuring the effect of sequential cropping (tomato and onion) on different arbuscular mycorrhiza (Glomus mosseae, Glomus fasciculatum, Glomus hoi and Glomus intraradices), the experiment was conducted in the screen house of the department of Plant Pathology, CCSHAU Hisar in 2020-2021. Seedling of tomato cv Selection 7 (Kharif season) was sown in the pots and sequential cropped with onion cv HO- 4 (Rabi season). When onion was grown sequentially after tomato, the study indicated that mycorrhizal colonisation in roots and sporocarp number in soil, plant growth parameters, mycorrhizal inoculation impact, and mycorrhizal count was highest in onion. In contrast to fertilization, cultivating specific crops in the previous season, such as tomatoes in this experiment, can stimulate arbuscular mycorrhizal colonization of onion roots, consequently enhancing plant growth.